PENERAPAN ALTMAN Z-SCORE MODIFIKASI UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN TEKNOLOGI DI BURSA EFEK INDONESIA - Syam, Nur Azisah; Muzakkir; Rahmaniarsih (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to analyze the potential for financial distress and the classification of financial health levels based on the Altman Z-Score model in technology sector companies listed on the Indonesia Stock Exchange (IDX). Using a purposive sampling technique, 24 technology companies were selected as the research sample over the 2021-2024 period. The research findings indicate the presence of potential financial distress in the technology sector, particularly in 2021, when several companies were classified within the distress zone. However, by 2024, an improvement was observed, with most companies maintaining Z-Score values above the safe threshold. Nevertheless, four companies maintained Z-Score values above the safe threshold. Nevertheless, four companies remain in the grey area and are approaching in the distress zone.